Dietary Supplementation of Coriander Seed, Turmeric Powder and Black Pepper and Its Effects on Performance, Health, Carcass Characteristics and Economics of Broiler Chickens - Nitinkumar A. Barad; H. H. Savsani; V. K. Karangiya (Journal of Scientific Research and Reports, 2026)
A six-week feeding trial was carried out to examine how dietary coriander seed, turmeric powder and black pepper influence feed intake, growth, feed efficiency, blood parameters, carcass traits, meat acceptability and the economics of broiler production. Two hundred and forty day-old chicks were randomly allocated to four dietary treatments, with three replicates of 20 birds each: unsupplemented control (T1), coriander seed at 2% (T2), turmeric powder at 2% (T3) and black pepper at 0.5% (T4). Feed intake and body weight were recorded weekly, while feed conversion ratio was calculated from cumulative feed intake and body weight gain. At the end of the trial, blood indices, carcass traits, organ weights and sensory attributes were assessed. Birds receiving the supplements consumed more feed overall than the control birds. The highest cumulative intake was recorded in the turmeric group (T3; 3422.00 ± 22.10 g/bird), followed by coriander (T2; 3367.90 ± 21.90 g), black pepper (T4; 3333.90 ± 21.80 g) and the control (T1; 3140.10 ± 22.95 g). Supplemented birds also finished the trial at higher body weights. The coriander group recorded the highest final body weight (1964.40 ± 31.61 g), compared with 1790.83 ± 23.64 g in the control, while black pepper and turmeric groups reached 1940.80 ± 31.30 and 1915.25 ± 34.26 g, respectively. Overall FCR did not differ significantly among treatments, although numerically lower values were observed in T2 and T4. Haemoglobin, PCV, TEC, TLC and ALT were not significantly affected, whereas AST was higher in all supplemented groups than in the control. Live weight, dressed weight, dressing percentage, visceral organ weights and sensory attributes were not significantly altered. The highest return over feed cost (Rs. 1825.60 per 60-bird batch) and profit per chick (Rs. 31.47) were obtained with coriander seed supplementation. Taken together, the results suggest that adding coriander seed at 2% offered the most favourable balance between growth performance and economic return under the conditions of this experiment. The supplementation did not produce detectable adverse effects on the carcass and haematological traits measured in the study.